1998
DOI: 10.1177/104225879802200203
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Socially Constructed Temporal Perspectives in the Emergence of Rapid-Growth Firms

Abstract: This study examined how owners and top management team members in firms that are growing very rapidly socially construct time so as to facilitate rapid growth. A blend of interview and text-based qualitative methods was used to study some firms that have achieved rapid growth and some that have yet to do so. Analysis led to the identification of several thematic patterns regarding the enactment of time. The first was simultaneity: informants appeared to sustain a simultaneous focus on the events actually occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 25 publications
0
36
0
1
Order By: Relevance
“…Education, risk acceptance, aspiration to grow, mid-management experience have been shown as important growth factors at the entrepreneur level [3]; [17]. At the company and strategy level, age and size of a company, strategic orientation, level of R&D, innovation are found to be relevant growth determinants [1], [10], [11], and [22]. Mateev and Anastasov [21] have shown that financial structure and productivity exert a positively influence on the potential for company growth.…”
Section: Review Of Previous Researchmentioning
confidence: 99%
“…Education, risk acceptance, aspiration to grow, mid-management experience have been shown as important growth factors at the entrepreneur level [3]; [17]. At the company and strategy level, age and size of a company, strategic orientation, level of R&D, innovation are found to be relevant growth determinants [1], [10], [11], and [22]. Mateev and Anastasov [21] have shown that financial structure and productivity exert a positively influence on the potential for company growth.…”
Section: Review Of Previous Researchmentioning
confidence: 99%
“…Many researchers utilising qualitative methods use the social constructionist label to define or position their work even though they are more concerned with the subjective experiences and perceptions of their respondents rather than the ways in which meanings are negotiated/shared through social processes contributing to the social construction of reality. So indeterminacy escalates as writers debate what it is that is being socially constructed (Hacking, 1999) whether this be time (Fischer et al 1997), meanings, identities, 'lived experiences' (Bruner, 1990;Denzin, 1997), the self (Gergen, 1999) or social reality (Berger and Luckmann, 1966). As a result, ideas about social construction are often misunderstood (for their linguistic reductionism, for example) and maligned (for their ability to be able to say another "solid" about social reality, for example).…”
Section: The Social Construction Of Reality: Ideas and Assumptionsmentioning
confidence: 99%
“…For example, Michael-Tsabari, Labaki and Zachary (2014) report that the search for foreign opportunities can be sparked by the fear that impending domestic legislation will open the door to foreign competitors. More fundamentally, entrepreneurs select exchange partners with temporal orientations similar to their own (Fischer, Reuber, Hababou, Johnson, & Lee, 1997) and there may be differing temporal orientations across countries that affect the pursuit of international opportunities (see Reinecke & Ansari, 2015). While international entrepreneurship researchers have studied temporality with respect to when foreign market entries are made, there has been little study, to our knowledge, of the temporal orientations of internationalizing firms, how their decision-makers perceive the windows of opportunities and how the opportunity-based processes they follow take these windows into consideration.…”
Section: Beyond Categorizationmentioning
confidence: 99%